The Ideology of Slavery : Proslavery Thought in the Antebellum South, 1830-1860 - Faust, Drew Gilpin (Book collections on Project MUSE., 1981)
In one volume, these essentially unabridged selections from the works of the proslavery apologists are now conveniently accessible to scholars and students of the antebellum South. The Ideology of Slavery includes excerpts by Thomas R. Dew, founder of a new phase of proslavery militancy; William Harper and James Henry Hammond, representatives of the proslavery mainstream; Thornton Stringfellow, the most prominent biblical defender of the peculiar institution; Henry Hughes and Josiah Nott, who brought would-be scientism to the argument; and George Fitzhugh, the most extreme of proslavery writer.